Characterization of Compass M-1 signals - Hauschild, A.; Montenbruck, O.; Sleewaegen, J.; Huisman, Lennard; Teunissen, Peter (Springer, 2012)
An analysis of observations from China's first medium earth orbit satellite Compass M-1 is presented, with main focus on the first orbit and clock solution for this satellite. The orbit is computed from laser ranging measurements. Based on this orbit solution, the apparent clock offset is estimated using measurements from two GNSS receivers, which allow Compass tracking. The analysis of the clock solutions reveals unexpectedly high dynamics in the pseudorange and carrier-phase observations. Furthermore, carrier-to-noise density ratio, pseudorange noise, and multipath are analyzed and compared to GPS and GIOVE. The results of the clock analysis motivate further research on the signals of the geostationary satellites of the Compass constellation.